Gender-based incidence, recovery period, and mortality rate of COVID-19 among the population of district Attock, Pakistan - Ejaz,R. (2023)
Abstract COVID-19 is reported as an extremely contagious disease with common symptoms of fever, dry cough, sore throat, and tiredness. The published literature on incidence and gender-wise prevalence of COVID-19 is scarce in Pakistan. Therefore, the present study was designed to compare the distribution, incubation period and mortality rate of COVID-19 among the male and female population of district Attock. The data were collected between 01 April 2020 and 07 December 2020 from the population of district Attock, Pakistan. A total of 22,962 individuals were screened and 843 were found positive for RT-qPCR for SARS-CoV-2. The confirmed positive cases were monitored carefully. Among the positive cases, the incidence of COVID-19 was 61.7% among males and 38.2% among females. The average recovery period of males was 18.89±7.75 days and females were 19±8.40 days from SARS-CoV-2. The overall mortality rate was 8.06%. The death rate of male patients was significantly higher (P<0.05) compared to female patients. Also, the mortality rate was higher (P<0.05) in male patients of 40-60 years of age compared to female patients of the same age group. Moreover, the mortality rate significantly increased (P<0.05) with the increase of age irrespective of gender. In conclusion, the incidence and mortality rate of COVID-19 is higher in males compared to the female population. Moreover, irrespective of gender the mortality rate was significantly lower among patients aged <40 years.